Contact and non-contact approaches in load monitoring applications using surface response to excitation method - ÜNAL, MUHAMMET (ELSEVIER SCI LTD, 2016)
Surface response to excitation (SuRE) method is a low-cost alternative to electromechanical impedance based structural health monitoring (SHM) technique. The SuRE method uses one piezoelectric transducer to excite the surface of a structure with a sweep sine wave. Piezoelectric sensors or scanning laser vibrometer can be used to monitor the dynamic response of structure. In this study, the performance of the SuRE method was evaluated with the conventional piezoelectric elements and scanning laser vibrometer used as contact and non-contact sensors, respectively, for monitoring the presence of loads on the surface. In order to determine the accuracy and reliability of both monitoring approaches in detecting changes in level of applied load, three different experimental setups were studied. Response of a system in the presence of a single load applying and multiple loads applying and its performance in detecting tightness in a nut and bolt system were investigated. The spectrum of the dynamic response is collected at the optimal operating condition. Any significant change of the spectral characteristics may indicate defects, improper loading or loose fasteners. The performance of the SuRE method using contact and non-contact sensors indicated that both variations of the method could be successfully used in load monitoring applications. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: SHM - structural health monitoring; Surface response to excitation method; Load monitoring; Piezoelectric; Laser Doppler; Vibrometer; Digital signal processor; ELECTROMECHANICAL IMPEDANCE; BEAMS; CRACK; IDENTIFICATION; VIBRATION